Researching feedback using a multi-experiment study. - Schroeder, Juliana (SAGE Publications, Ltd., 2024)
Juliana Schroeder, PhD, associate professor, University College Berkeley, discusses researching feedback using a multi-experimental study, including participant recruitment, data collection, and research findings.